Dormancy of metastatic melanoma - Ossowski, Liliana (2009)
Metastatic dormancy of melanoma has not received sufficient attention, most likely because once detectable, metastasis is almost invariably fatal and, understandably, the focus has been on finding ways to prolong life of patients with overt recurrences. Nevertheless, analysis of the published clinical and experimental data on melanoma indicates that some aspect of melanoma biology imitate traits recently associated with dormancy in other solid cancers. Among them the ability of some melanomas to disseminate early during primary tumor progression and once disseminated, to remain undetected (dormant) for years. Comparison of cutaneous and uveal melanoma indicates that, in spite of being of the same origin, they differ profoundly in their clinical progression. Importantly for this discussion, between 40 and 50% of uveal melanoma remain undetected for longer than a decade, while less than 5% of cutaneous melanoma show this behavior. Both types of melanoma have activating oncogene mutations that provide autonomous pro-proliferative signals, yet the consensus is that those are not sufficient for tumor progression. If that is the case, it is possible to envision that signals from outside the tumor cell, (microenvironment) shape the fate of an individual disseminated cell, regardless of an oncogene mutation, to progress or to pause in a state of dormancy. To stimulate further debate and inquiry we describe here a few examples of potential signals that might modify the fate of disseminated cell and provide brief description of the current knowledge on dormancy in other cancers. Our hope is to convince the reader that disseminated melanoma cells do enter periods of prolonged dormancy and that finding ways to induce it, or to prolong it, might mean an extension of symptoms-free life for melanoma patients. Ultimately, understanding the biology of dormancy and the mechanisms of dormant cell survival, might allow for their specific targeting and elimination.